Egyptian Financial Supervisory Authority (EFSA) Authority's Board of Directors Resolution No. 158 of the year 2014 Issued on 3/12/2014 Regarding Micro-finance Fields and the Value Thereof = الهيئة العامة للرقابة المالية قرار مجلس إدارة الهيئة رقم 158 لسنة 2014 بتاريخ 3/12/2014 بشأن مجالات التمويل متناهى الصغر وقيمته - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic